2002
DOI: 10.1093/emboj/cdf689
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VIIa, harmonin and cadherin 23, three Usher I gene products that cooperate to shape the sensory hair cell bundle

Abstract: contributed equally to this work Deaf-blindness in three distinct genetic forms of Usher type I syndrome (USH1) is caused by defects in myosin VIIa, harmonin and cadherin 23. Despite being critical for hearing, the functions of these proteins in the inner ear remain elusive. Here we show that harmonin, a PDZ domain-containing protein, and cadherin 23 are both present in the growing stereocilia and that they bind to each other. Moreover, we demonstrate that harmonin b is an F-actin-bundling protein, which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
526
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(555 citation statements)
references
References 45 publications
22
526
1
6
Order By: Relevance
“…However, we do detect a phenotypic effect of a presumed 50% reduction in the amount of functional Cdh23 in the adult cochlea. It may be that Cdh23 elsewhere in the hair cell mediates the effects we see or that only small amounts of Cdh23 protein are present in mature stereocilia, below the detection limits of the technique used by Boeda et al (2002). Alternatively, in Cdh23 v heterozygotes, the stereocilia bundle may not attain maximum strength because of the proposed transient links being compromised during development.…”
Section: Age-related Hearing Lossmentioning
confidence: 93%
See 3 more Smart Citations
“…However, we do detect a phenotypic effect of a presumed 50% reduction in the amount of functional Cdh23 in the adult cochlea. It may be that Cdh23 elsewhere in the hair cell mediates the effects we see or that only small amounts of Cdh23 protein are present in mature stereocilia, below the detection limits of the technique used by Boeda et al (2002). Alternatively, in Cdh23 v heterozygotes, the stereocilia bundle may not attain maximum strength because of the proposed transient links being compromised during development.…”
Section: Age-related Hearing Lossmentioning
confidence: 93%
“…These links are thought to be important in holding the stereocilia bundle together. Boeda et al (2002) recently reported that Cdh23 could not be detected in stereocilia of mice older than post natal day 30, suggesting that Cdh23 could be involved in crosslinking only developing stereocilia. However, we do detect a phenotypic effect of a presumed 50% reduction in the amount of functional Cdh23 in the adult cochlea.…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the proteins directly involved in ion transport, there is increasing evidence that protein scaffolds play important roles in cochlear function (Verpy et al 2000;Davies et al 2001;Boeda et al 2002;Mburu et al 2003;Bao et al 2004;Belyantseva et al 2005;Kikkawa et al 2005). For example, the postsynaptic density of the 95-kDa-disc large-zona occludens-1 (PDZ) domain protein harmonin has been shown to anchor cadherin 23 to the stereocilia microfilaments and is thought to contribute to shaping the hair bundle (Boeda et al 2002).…”
Section: Introductionmentioning
confidence: 99%